Gender and the contemporary educational canon in the UK - Elliott, V (Universidad de Murcia, 2017)
This paper presents an analysis of the gender of the authors and the main characters of the set texts for English examinations taken at age 16 in England, Northern Ireland, Scotland and Wales. It presents an argument for why representation within the canon is important and places this within the context of recent educational reform in England and Scotland. The analysis demonstrates that texts by female authors are in a minority, sometimes in the extreme, and when the gender of the main character is taken into account, there is an even greater imbalance. The reasons behind this, even after a time of major educational reform, are explored and the constraints of the market are suggested as reasons why greater risks were not taken.